Adsorption of grape pomace (Vitis vinifera) and pecan shell (Carya illinoensis) phenolic compounds to insoluble dietary fiber - SUBIRÍA-CUETO,Carlos Rodrigo (2022)
Abstract Grape pomace (GP) and pecan shell (PS) are agro-industrial by-products rich in healthy bioactives, mainly phenolic compounds (PC) and dietary fiber (DF). Raw GP and PS were chemically characterized, and the adsorption isotherms of their PC-insoluble DF (IDF) complexes were evaluated. GP and PS statistically differed (p < 0.05) in chemical and physicochemical properties. Total PC, total flavonoids, and IDF were higher in GP. Thirteen and eight PC were identified in GP and PS by HPLC-MS/MS chromatography, finding isoquercetin and type B dimer and trimer procyanidins as the most abundant compounds. PC-IDF (phenolic compounds-insoluble dietary fiber) adsorption isotherms were determined by both spectroscopic (Freundlich) and HPLC-MS/MS (Freundlich/Langmuir) techniques, observing that PS IDF presented higher PC adsorption at all tested concentrations. Epicatechin, isoquercetin, and quercetin were the main identified PC in both by-products, and were able to fit to both Langmuir and Freundlich isotherm by HPLC-MS/MS.